Enhancing the Green Purchase Intention Based on Green Marketing: An Empirical Study from Pakistan - Rizwan, Muhammad; Ahmad, Shahzad Ubair; Mehboob, Najma (Asian Journal of Empirical Research, 2013)
In recent days, the companies are extensively using technology for the promotion of green marketing. This study aims to explore the factors that affect purchase intention and its build up a conceptual model to inspect the influence of three preceding factors (green perceived value, green perceived risk, and trust) on purchase intention based green marketing. Data is collected from 150 respondents through self-administered questionnaires. The usable questionnaires were entered in the SPSS for regression analysis. Results of the study show significant relationship of perceived value and perceived risk with trust and trust to purchase intention. On other side green perceived value and green perceived risk significantly affect green purchase intention. The study did not find any relationship between value and risk. The results indicate the relative importance of three preceding factors of perceived value, perceived risk and trust towards green marketing. These factors influence the green purchase intention.